MANGROVE FOREST EFFECT ON THE COASTLINE IN RANGSANG ISLAND RIAU PROVINCE - Nadeak, Paulinus; Mubarak, Mubarak; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2020)
The study was conducted in May-June 2019 on Rangsang Island. This study aims to determine the effect of mangrove forests on coastline found on the island of Rangsang in Riau Province. The sampling location was determined by purposive sampling, namely 3 station points, namely Segomeng Village, Tanjung Kedabu Village, and Sungai Gayung Kiri Village. Landsat image data analyzed at the Oceanographic Physics Laboratory of the Department of Marine Sciences, Faculty of Fisheries and Maritime Affairs, University of Riau. To find out the area of ​​mangroves using Landsad 5 TM satellite imagery and Landsat 8 OLI Tirs imagery and analyzed using Er Mapper Software, Envi 4.5 and Arcgis 10.3. Calculation of the structure of the mangrove community is carried out using the line plot plot method. The results of the analysis of the vast landsat image of mangroves in the coastal areas of Rangsang Island in 1997, 2002, 2007, 2013, 2019 were respectively 11,093 ha, 10,807 ha, 10,393 ha, 10,121 ha and 9,971 ha. Changes in the coastline indicate the occurrence of abrasion and accretion, where the highest abrasion occurs at station three with an average of -7.6 m/year and accretion occurs at station one with an average of 2.68 m / year. Mangrove density at station one is 2266.7 ind / ha and at station two that is 1466.7 ind / ha. Mangrove species found were Rhizophora apiculata, Rhizophora mucronata, Avicennia alba, Sonneratia ovata, Bruguiera gymnorrhiza, and Xylocarpus granatum.